2015
DOI: 10.1002/2014gb004919
|View full text |Cite
|
Sign up to set email alerts
|

Phenological characteristics of global coccolithophore blooms

Abstract: Coccolithophores are recognized as having a significant influence on the global carbon cycle through the production and export of calcium carbonate (often referred to as particulate inorganic carbon or PIC). Using remotely sensed PIC and chlorophyll data, we investigate the seasonal dynamics of coccolithophores relative to a mixed phytoplankton community. Seasonal variability in PIC, here considered to indicate changes in coccolithophore biomass, is identified across much of the global ocean. Blooms, which typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 65 publications
9
82
0
Order By: Relevance
“…However, here we observed a typical North Atlantic community of coccolithophores (Savidge et al, 1995;Dale et al, 1999;Poulton et al, 2010), growing alongside the ICB diatom bloom, rather than just succeeding the diatoms. This is consistent with the rising tide hypothesis of Barber and Hiscock (2006), as well as observations from both in situ (Leblanc et al, 2009) and satellite measurements (Hopkins et al, 2015) suggesting that coccolithophores are present in North Atlantic spring blooms. Despite the contrasting environment and overall community structure of the NWB, the coccolithophore dynamics were similar, appearing independent of the overall community dynamics.…”
Section: Relative Independence Of the Coccolithophore Communitysupporting
confidence: 90%
“…However, here we observed a typical North Atlantic community of coccolithophores (Savidge et al, 1995;Dale et al, 1999;Poulton et al, 2010), growing alongside the ICB diatom bloom, rather than just succeeding the diatoms. This is consistent with the rising tide hypothesis of Barber and Hiscock (2006), as well as observations from both in situ (Leblanc et al, 2009) and satellite measurements (Hopkins et al, 2015) suggesting that coccolithophores are present in North Atlantic spring blooms. Despite the contrasting environment and overall community structure of the NWB, the coccolithophore dynamics were similar, appearing independent of the overall community dynamics.…”
Section: Relative Independence Of the Coccolithophore Communitysupporting
confidence: 90%
“…However, by looking at the total Chla provided by satellite no information about the phytoplankton community composition (and changes in) is provided [72]. In this study we were able to look specifically at the diatom biomass by using a satellite-derived diatom concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Margalef, 1978;Holligan et al, 1983;Lochte et al, 1993;Sieracki et al, 1993;Thunell et al, 1996;Balch, 2004). Indeed, a recent study of the phenological characteristics of coccolithophore blooms by Hopkins et al (2015) concluded that they often follow those of diatoms in many regions, with the sequencing driven by increasing stabilisation and/or nutrient depletion (mainly silicate and/or iron and possibly also favoured by an associated increase in carbonate saturation; Merico et al, 2004) of the surface layer. The slightly different seasonal pattern observed at both sampling depths (Fig.…”
Section: Seasonal Dynamics Of the Calcareous And Siliceous Phytoplankmentioning
confidence: 99%